Photovoltaic System Loads Analysis for Low/Middle Income Earners in Afikpo, Ebonyi State, Nigeria. (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Unreliable electricity supply remains a persistent challenge in many developing countries, disproportionately affecting low- and middle-income households through frequent power outages and rising energy costs. This study assessed household electrical energy demand and determined the optimal sizing of stand-alone photovoltaic (PV) systems for low- and middle-income households in Afikpo, Ebonyi State, Nigeria.A total of 100 households participated in the study, comprising 50 low-income households (monthly income of ₦50,000–₦150,000) and 50 middle-income households (monthly income of ₦150,000–₦500,000). A structured load survey was conducted to collect data on household appliances, including their quantities, rated power, and average daily operating hours. Daily energy demand was estimated from the load survey, and PV systems were designed using standard engineering procedures based on daily energy consumption, average peak sunshine hours, system de-rating factor, battery storage requirements, and inverter capacity. The economic viability of the proposed systems was evaluated using installation cost estimates and simple payback period analysis.The results show that low-income households consume an average of 2.15 kWh/day and can be adequately served by a 600 W stand-alone PV system comprising two 300 W solar modules, a 48 V, 150 Ah battery bank, and a 1 kW pure sine wave inverter. Middle-income households recorded an average daily energy demand of 5.48 kWh/day, requiring a 1.5 kW PV system consisting of three 500 W solar modules, a 48 V, 300 Ah battery bank, and a 2 kW pure sine wave inverter. Economic analysis indicates that the proposed systems are financially attractive, with estimated payback periods of approximately three years, depending on household energy consumption and prevailing component costs.The findings confirm that household income level significantly influences electricity demand and PV system sizing requirements. The study demonstrates that properly designed stand-alone photovoltaic systems provide a technically feasible, economically viable, and environmentally sustainable solution for improving residential electricity access in semi-urban Nigeria. The results provide practical design guidelines for engineers, researchers, policymakers, and energy planners involved in residential renewable energy deployment.